Pedagogical renewal: Improving the quality of classroom interaction in Nigerian primary schools - Hardman, Frank; Abd-Kadir, Jan; Smith, Fay (International Journal of Educational Development, 2008)
This study reports on an investigation of classroom interaction and discourse practices in Nigerian primary schools. Its purpose was to identify key issues affecting patterns of teacher–pupil interaction and discourse as research suggests managing the quality of classroom interaction will play a central role in improving the quality of teaching and learning, particularly in contexts where learning resources and teacher training are limited. The study was based on the interaction and discourse analysis of video recordings of 42 lessons and 59 teacher questionnaires from 10 States, drawn mainly from the north of Nigeria. The findings revealed the prevalence of teacher explanation, recitation and rote in the classroom discourse with little attention being paid to securing pupil understanding. The wider implications of the findings for improving the quality of classroom interaction in Nigerian primary schools through more effective school-based training are considered.
00109 KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2007.02.008 10/cq6k4z 2129771:4Y992QRW 261495:A886PDXT